1995
DOI: 10.1111/j.1365-2249.1995.tb06660.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in neutrophil accumulation in mice is not mediated through immigrant regulatory cells

Abstract: SUMMARYGenetic variation of induced peritoneal neutrophiiia in mice was accompanied by parallel variation in macrophage responses. The timing of the macrophage responses in high responder (C57B1/10) mice indicated a potential role for these cells in mediating the enhanced neutrophil response. However, adoptive transfer of inflammatory macrophages did not induce neuirophilia. Analysis of peritoneal cytokine levels in high and low responder mice further indicated [hat IL-I. lL-3. GM-CSE, G-CSE and interferon-gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Eight-to 12-week-old, sex-matched C3H donor mice received a 2 Gy TBI or were left unirradiated. After 1 day, 1 ml of thioglycolate (3%, AppliChem; Marley et al, 1995) were injected intraperitoneally (i.p.). Peritoneal macrophages were collected by peritoneal lavage after 3 days and 5 3 10 6 doses were injected i.v.…”
Section: Macrophage Transfermentioning
confidence: 99%
“…Eight-to 12-week-old, sex-matched C3H donor mice received a 2 Gy TBI or were left unirradiated. After 1 day, 1 ml of thioglycolate (3%, AppliChem; Marley et al, 1995) were injected intraperitoneally (i.p.). Peritoneal macrophages were collected by peritoneal lavage after 3 days and 5 3 10 6 doses were injected i.v.…”
Section: Macrophage Transfermentioning
confidence: 99%
“…Previous studies have demonstrated decreased total leukocyte recruitment to the peritoneum in Mgat5 Ϫ/Ϫ mice after exposure to TG (31). However, it is important to note that the end point of the study as well as the mouse strain were different compared with the current study (3 h versus 6 h), and strain-related differences are known to exist during induced neutrophilia in mice (32). In the TG-exposed Mgat5 Ϫ/Ϫ mice in our study, we did not observe a significant reduction in eosinophil recruitment compared with WT counterparts (p ϭ 0.1), although the trend in reduction paralleled the BALF eosinophils in the allergen challenge model (Fig.…”
Section: Volume 286 • Number 44 • November 4 2011mentioning
confidence: 60%